kGEM: An EM-based algorithm for local reconstruction of viral quasispecies - Artyomenko, Alexander; Mancuso, Nicholas; Zelikovsky, Alex; Skums, Pavel; Mandoiu, Ion (2013 IEEE 3rd International Conference on Computational Advances in Bio and Medical Sciences (ICCABS), 2013)
The main challenge in local viral quasispecies reconstruction is to eliminate sequencing errors while preserving the natural heterogeneity of the viral population. This paper presents a new approach to error correction via an expectation maximization (EM) method.